Constitutional law, being the seventh edition of Ridge's Constitutional law of England - Berriedale Keith, Arthur (London : Stevens and Sons, 1939)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: grondwettelijk recht; Groot-Brittannië.